Association of elevated albumin-corrected anion gap with all-cause mortality risk in atrial fibrillation: a retrospective study - Jia Xu; Zhen Wang; Yun Wang; Xinran Chen; Lan Ma; Xiaochen Wang (BMC Cardiovascular Disorders)
Abstract Background Compared to the conventional anion gap, the albumin-corrected anion gap (ACAG) offers a more precise measure of acid-base imbalance, providing superior prognostic insight. However, the prognostic relevance of ACAG in individuals of atrial fibrillation (AF) remains insufficiently explored. This research seeks to evaluate the correlation between ACAG levels and mortality risk in individuals with AF. Methods We identified individuals diagnosed with AF from the Medical Information Mart for Intensive Care (MIMIC)-IV database. Participants were categorized into quartiles based on their ACAG levels. The outcomes included 30 days and 365 days all-cause mortality. Kaplan–Meier survival curves were utilized to evaluate cumulative survival across the ACAG quartiles. We applied Cox regression and restricted cubic spline regression analyses to evaluate the correlation between ACAG levels and prognosis. Subgroup analyses and interaction assessments were applied to confirm the robustness of the findings. Results A total of 2920 AF patients (54.93% male) were incorporated into the analysis, with 1.61% identified as having paroxysmal AF. The 30-day and 365-day mortality rates were 22.91% and 39.21%, respectively. Kaplan–Meier survival curves demonstrated that elevated ACAG levels were significantly linked to increased mortality (log-rank P < 0.001). In multivariate Cox proportional hazards analyses, increased ACAG independently predicted mortality at both 30 days (adjusted hazard ratio [aHR], 1.04; 95% CI, 1.02–1.05; P < 0.01) and 365 days (aHR, 1.03; 95% CI, 1.02–1.05; P < 0.01) after adjusting for potential confounders. A positive relationship between rising ACAG levels and mortality risk was showed by restricted cubic spline analysis. Subgroup analyses revealed no significant interactions (all interaction P-values > 0.05). Conclusions In individuals with AF, higher ACAG levels are related to a greater mortality risk at 30 and 365 days. These findings suggest that ACAG may serve as a valuable prognostic marker for AF patient stratification. Incorporating ACAG into clinical decision-making could support improved therapeutic strategies and enhance patient outcomes.